Reclaiming justice the International Tribunal for the former Yugoslavia and local courts - d; Hagan, John, 1946- (New York ; Oxford : Oxford University Press, 2011)
This volume adds to prior literature about the ICTY by providing a comprehensive view of how people from Bosnia and Herzegovina Croatia, Kosovo, and Serbia view and evaluate the ICTY.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: International Tribunal for the Prosecution of Persons Responsible for Serious Violations of International Humanitarian Law Committed in the Territory of the Former Yugoslavia since 1991.; Yugoslav War Crime Trials, Hague, Netherlands, 1994-; Yugoslav War, 1991-1995 -- Atrocities; War crimes -- Former Yugoslav republics